Analisis Risiko Penggilingan Padi Kecil (Studi Kasus Penggilingan Padi SB, Kecamatan Karawang Barat, Kabupaten Karawang, Jawa Barat) - Azzahra, Lissa; Heryanto, Mahra Arari; Renaldi, Eddy; Yudha, Eka Purna (Universitas Galuh, 2025)
SB Rice Mill has a rice yield of 62 kg, which is below the national average yield of 65 kg, also quality of rice is often not in accordance with consumer demand. Both of these lead to losses in the production process that are not handled properly. These risks disrupt performance and hinder the goal to produce rice with good quality and quantity. Therefore, research related to risk analysis was conducted at SB Rice Mill with a qualitative approach and case study. This research was conducted with the aim of identifying risks and the best mitigation actions against these risks through the House of Risk stages 1 and 2. The results showed that there were 19 risk events from 32 risk agents in the rice production process at SB Rice Mill. 13 risk agents are considered as the main cause of the overall risk occurrence which will be handled. Then 21 mitigation actions were identified that need to be carried out.